Agarum clathratum Inhibits LPS-induced IL-1β Expression through the Regulation of the JNK/c-Jun Signaling Pathway - Han, Jung-Min; Cho, Sung-Dae; Chung, Gehoon; Choi, Su-Jung; Shin, Ji-Ae; Hong, Seong-Doo; Hong, Kyoung-Ok (The Korean Journal of Oral and Maxillofacial Pathology, 2021)
Agarum clathratum (A. clathratum) is a marine brown algal species that belongs to the Costariaceae family and has antioxidant and anti-microbial properties. However, the anti-inflammatory effects of A. clathratum and the molecular mechanisms involved have not been determined so far. This study aimed to investigate the anti-inflammatory effects of A. clathratum extracts in THP-1 macrophages stimulated by lipopolysaccharide (LPS) derived from Porphyromonas gingivalis. The THP-1 cells were differentiated with 12-O-tetradecanoylphorbol-13-acetate and treated with A. clathratum before LPS stimulation. Cell viability was assessed using the trypan blue exclusion assay. The expression of pro-inflammatory response-associated molecules was evaluated by quantitative real-time polymerase chain reaction and Western blot analysis. A. clathratum treatment inhibited the expression of interleukin-1β in LPS-stimulated THP-1 macrophages without causing any cytotoxicity. The anti-inflammatory effect of A. clathratum resulted in a significant repression of the JNK/c-Jun signaling axis, a key regulator in inflammation responses. This study highlights the possible role of A. clathratum in the inhibition of pro-inflammatory cytokines via suppression of the JNK/c-Jun signaling axis and suggests that A. clathratum could serve as a marine-derived anti-inflammatory agent in periodontitis. KCI Citation Count: 0